Human Epicardial Fat Expresses Glucagon-Like Peptide 1 and 2 Receptors Genes - Iacobellis, Gianluca; Camarena, Vladimir; Sant, David W.; Wang, Gaofeng (Hormone and Metabolic Research, 2017)
Epicardial adipose tissue (EAT) is an easily measurable visceral fat of the heart with unique anatomy, functionality, and transcriptome. EAT can serve as a therapeutic target for pharmaceutical agents targeting the fat. Glucagon-like peptide-1 (GLP-1) and GLP-2 analogues are newer drugs showing beneficial cardiovascular and metabolic effects. Whether EAT expresses GLP- 1 and 2 receptors (GLP-1R and GLP-2R) is unknown. RNA-seq analysis and quantitative real-time polymerase chain reaction (qRT-PCR) were performed to evaluate the presence of GLP-1R and GLP-2R in EAT and subcutaneous fat (SAT) obtained from 8 subjects with coronary artery disease and type 2 diabetes mellitus undergoing elective cardiac surgery. Immunofluorescence was also performed on EAT and SAT samples using Mab3f52 against GLP-1R. Our RNA-sequencing (RNA-seq) analysis showed that EAT expresses both GLP-1R and GLP-2R genes. qRT-PCR analysis confirmed that GLP-1R expression was low but detected by 2 different sets of intron-spanning primers. GLP-2R expression was detected in all patients and was found to be 5-fold higher than GLP-1R. The combination of accurately spliced reads from RNA-seq and successful amplification using intron-spanning primers indicates that both GLP-1R and GLP-2R are expressed in EAT. Immunofluorescence clearly showed that GLP-1R is present and more abundant in EAT than SAT. This is the first time that human EAT is found to express both GLP-1R and GLP-2R genes. Pharmacologically targeting EAT may induce beneficial cardiovascular and metabolic effects.